The Effect of Using Flashcard Media on Students’ Vocabulary Mastery at the 7th Grade of MTs Zainul Hasan Sambirejo, Pare, Kediri - Kadnawi; Sofie Rohmatul Fauziah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
This study aims to know the effect of using flashcard media on students’ vocabulary mastery at the 7th Grade of MTs Zainul Hasan Sambirejo, Pare. Design used was pre experimental research pre-test post-test one group only. Sample taken was 32 from 82 population by using simple random sampling. To collect the data, the researcher used vocabulary written test with 25 items in multiple-choice format. In analyzing data, she used IBM SPSS statistic versions. 25 application of paired-sample t.test. It aims to know whether there is or not a significant difference between before given the treatment and after given the treatment using flashcard media on students’ vocabulary mastery. After collecting and calculating data, she found that mean of pre-Test 72.06, mean of post-Test 91.38, median of pre-test 82, median of post-test 96, mode of pre-test 84 and mode of post-test 100. In testing the hypothesis, she used t-test formula. She found that p value Sig (2-tailed)= 0.000 < 0.05, at the level significance of df = 31. So, the null hypothesis was rejected and the alternative hypothesis could be accepted. It means that using flashcard media affects students’ vocabulary mastery at the 7th Grade of MTs Zainul Hasan Sambirejo, Pare, Kediri